S dyslexiou k vysokoškolskému titulu: Naratívna syntéza - Karin Černickaja; Lenka Sokolová (Karolinum Press, 2024)
Learning disabilities, specifically dyslexia, affect learning processes and school performance of pupils and students at all levels of education. The aim of this narrative synthesis is to outline the topics that are investigated in relation to the university studies of people with dyslexia, while the mapping of this empirical knowledge has the potential to reflect these studies at their different stages. From 923 studies registered between 2001 and 2020 in the Web of Science database, we included 65 studies, which represent an overview of knowledge about decisions about university studies, adjustment in the university environment, study strategies of individuals with dyslexia and support that is provided by university. The results show that dyslexia and its symptoms can be a barrier to successful university studies, yet these students can overcome these barriers with adequate support.